The library marketing toolkit - Potter, Ned, 1980- (London : Facet Publishing, 2012)
This practical guide offers coverage of every element of library marketing and branding for all sectors, including archives and academic, public and special libraries.
This is a toolkit of ideas to inspire action. As libraries continue to fight for their survival amid growing expectations, competition from online sources and wavering public perceptions, effective marketing is increasingly becoming a critical tool to ensure the continued support of users, stakeholders and society as a whole. This unique practical guide offers expert coverage of every element of library marketing and branding for all sectors including archives and academic, public and special libraries. Packed with globally-sourced case studies from thought-leaders and those at the cutting edge of library marketing it provides innovative and easy-to-implement techniques and ideas. The key topics covered are: marketing strategy; essential marketing tools and techniques; getting the most out of social media; marketing on a budget; library branding; marketing to internal stakeholders and with third parties; marketing special collections and archives; and, library advocacy as marketing.
Introduction : About marketing -- Seven key concepts for marketing libraries : The seven concepts ; Anchoring these ideas in marketing theory -- Strategic marketing : The marketing cycle ; 1. Decide on your goals ; 2. Market research ; 3. Segmentation ; 4. Set objectives ; 5. Promotional activities ; 6. Measurement ; 7. Evaluation ; 8. Modification -- Developing a marketing plan -- The library brand : Quick definitions ; What is library branding? ; Visual identity ; Merchandise ; Slogans ; Branding and marketing a converged library and IT service -- Marketing and the library building : Library design ; Signs and displays ; Marketing the library as space -- An introduction to online marketing : The library website ; Search Engine Optimization (SEO) ; Mobile websites ; E-mail -- Marketing with social media : Do your patrons use social media? ; General principles of marketing with social media ; Twitter ; Facebook ; Blogs and blogging ; Tumblr ; Google+ ; LinkedIn ; Conclusion -- Marketing with new technologies : Quick definitions ; Video marketing ; Image sharing ; QR codes ; Geolocational apps ; Web 2.0 catalogues and live chat ; Podcasts Wikis ; Slide sharing ; Viral marketing ; Technology and teenagers -- Marketing and people : Collaborating with people ; Reaching people -- Internal marketing : The importance of internal marketing ; Marketing to internal stakeholders ; Marketing with internal stakeholders: co-operative promotion -- Library advocacy as marketing : National campaigns and localPromotingg ; Pormoting your library incriticisme to citicism of libraries in general ; Advocacy, positiveand possitive messages ; The library media narrative ; Trojan horse advocacy -- Marketing special collections and archives : Introduction ; Access, access, access: marketing digital collections ; Genealogy ; Tailoring your marketing to fit the cultural landscape ; Mounting and promoting a more traditional exhibition ; Learning from museums ; Crowdsourcing ; Marketing audiovisual materials -- A final word on marketing libraries -- Appendix: Glossary of Web 2.0 tools and platforms.
Includes bibliographical references (p. [201]-203) and index.
Keywords: Libraries -- Marketing; Branding (Marketing) -- Libraries; Libraries -- Public relations; Advertising -- Libraries